Angiosarcoma of Small Bowel Presenting with Obstruction: Novel Observations on a Rare Diagnostic Entity with Unique Clinical Presentation. (21st October 2012) - Siderits, Richard; Poblete, Frederick; Saraiya, Biren; Rimmer, Cheryl; Hazra, Anup; Aye, Le
Abstract : We present a case of angiosarcoma in small bowel, presenting with partial small bowel obstruction in a 79-year-old man with no history of radiation, chemotherapy, toxin exposure, or previous operative intervention. Angiosarcoma of small bowel is a rare entity which may present with nausea, abdominal pain, recurrent bleeding, and usually a history of prior radiation or exposure to specific toxins (polyvinyl chloride). Angiosarcoma of small bowel tends to spread rapidly and has a poor prognosis. We review the surgical and oncologic challenges. We report unique macroscopic findings of raised hyperemic margins, which are suggestive of a vasogenic lesion and the histologic feature of a partially retiform pattern with dense basement membrane material in an otherwise poorly differentiated lesion.